Laser wire welding process for hot-formed steel with aluminum coating
By applying a volatile non-aqueous dispersion of rare earth metal powder to the joint end surface of aluminum-coated hot-formed steel plates and performing laser filler wire welding, the problem of reduced mechanical properties caused by aluminum elements entering the weld was solved and achieved High mechanical strength and toughness of the weld.
Patent Information
- Application Number
- CN202411487095.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-24
AI Technical Summary
During the welding process of aluminum-coated thermoformed steel, aluminum elements are prone to enter the weld, resulting in the formation of δ ferrite and reducing the mechanical properties of the weld.
A volatile non-aqueous dispersion containing rare earth metal powder is applied to the joint end surface of the aluminum-coated hot-formed steel plate to be welded, and laser wire filling welding is performed after the dispersion evaporates. The rare earth metal melts at high temperature and adheres to the joint end surface, capturing aluminum atoms to form a solid solution, refining the grains and suppressing crystal dislocation.
It effectively prevents aluminum elements from entering the weld, prevents the formation of low-strength delta ferrite, and improves the mechanical strength and toughness of the weld. The resulting weld joint has both good fracture strength and plasticity.
Smart Images

Figure CN118989493B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hot-formed steel welding, and in particular to a laser wire-filling welding process for hot-formed steel containing an aluminum coating. Background Art
[0002] The following content in the background technology refers only to the information related to the present invention understood by the inventor, and is intended to increase the understanding of the present invention by explaining some basic technical knowledge related to the present invention. This information does not necessarily constitute knowledge known to ordinary technicians in this field.
[0003] Hot-formed steel refers to steel plates or strips used for direct and indirect hot stamping. The original structure of hot-formed steel is ferrite and pearlite. After heat treatment, it is quickly stamped and cooled to form a martensite structure, which greatly improves the strength of the steel plate. Hot-formed steel has been widely used in the automotive field. It not only improves the collision resistance and overall safety of the vehicle body, but also effectively reduces the weight of the vehicle and reduces energy consumption. In order to prevent oxidation and decarburization of the surface of hot-formed steel during the hot stamping process, a layer of coating is usually plated on the surface of the hot-formed steel, including common Al-Si coatings, Zn-Ni coatings, etc.
[0004] For Al-Si coated hot-formed steel, the Al in the coating easily enters the weld during welding to induce the formation of delta ferrite, which has low strength and leads to deterioration of the mechanical properties of the weld joint. In order to overcome the above problems, one method currently used is to remove the Al-Si coating on the surface of the hot-formed steel to be welded by mechanical stripping or laser ablation, and then weld. However, this method is not only costly, but also inefficient and not suitable for industrial application. Therefore, it is necessary to further explore the welding process of hot-formed steel containing aluminum coating. Summary of the invention
[0005] In view of the above problems, the present invention provides a laser wire welding process for hot-formed steel with aluminum coating, which does not require the removal of the aluminum coating on the surface of the hot-formed steel before welding, and can effectively avoid the problem of the aluminum coating deteriorating the mechanical properties of the hot-formed steel weld, and the obtained weld joint has good fracture strength and plasticity. To achieve the above invention purpose, the present invention discloses the following technical solutions:
[0006] A laser wire welding process for hot-formed steel containing an aluminum coating comprises the following steps:
[0007] (1) A volatile non-aqueous dispersion containing rare earth metal powder is applied to the joint end faces of the aluminum-coated hot-formed steel plates to be welded.
[0008] (2) Then, the joints of the two hot-formed steel plates are butted together to form a gap between them. After the dispersion liquid has evaporated, the laser wire welding process is used for welding.
[0009] Furthermore, in step (1), the content of the rare earth metal powder in the dispersion is 30-50 g / L. Optionally, the fineness of the rare earth metal powder is not less than 100 mesh, such as 100-200 mesh.
[0010] Furthermore, in step (1), the rare earth metal includes at least one of lanthanum, cerium, yttrium, samarium, ytterbium, etc.
[0011] Furthermore, in step (1), the volatile non-aqueous dispersion includes a mixture of at least one of anhydrous methanol, anhydrous ethanol, etc. and propylene glycol or glycerol. Optionally, the volume ratio of the two is 1:0.25-0.4.
[0012] Preferably, in step (1), the rare earth metal powder is a pre-treated metal powder prepared by the following method: (i) dispersing the rare earth metal powder into a volatile non-aqueous solvent, then adding a silane coupling agent and an acrylic acid monomer and stirring, and separating the solid matter after completion. (ii) adding the solid matter into a volatile non-aqueous solvent again, and heating and stirring until the non-aqueous solvent is volatilized and removed, thereby obtaining the pre-treated metal powder.
[0013] Furthermore, in steps (i) and (ii), the material-liquid ratio of the rare earth metal powder, solid matter and non-aqueous solvent is 1 g: 10-30 ml. Optionally, the non-aqueous solvent includes at least one of anhydrous methanol, anhydrous ethanol, isopropanol and the like.
[0014] Furthermore, in step (i), the mass fraction of the silane coupling agent in the non-aqueous solvent is 0.02-0.035%. Optionally, the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, octadecyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, etc.
[0015] Furthermore, in step (i), the mass fraction of the acrylic acid monomer in the non-aqueous solvent is 0.1-0.18%.
[0016] Furthermore, in step (i), the stirring time is not less than 10 min, such as 10 min, 20 min, etc.
[0017] Furthermore, in step (ii), the heating temperature is 60-80°C.
[0018] Furthermore, in step (2), the width of the gap is 0.5-1 mm. The welding wire of the laser wire welding process can be a commercially available product or other existing product, and the present invention is not particularly limited.
[0019] Furthermore, in step (2), the power of the laser wire welding process is 3000-8000 W. The welding speed is 0.5-1.5 m / min, and the shielding gas flow rate is 10-15 L / min.
[0020] Compared with the prior art, the present invention has at least the following beneficial technical effects:
[0021] (1) The aluminum element in the coating is easy to enter the weld pool when welding between hot-formed steel plates containing aluminum coatings, causing the formation of low-strength delta ferrite during the cooling process, thereby reducing the strength of the welded joint. The present invention applies a volatile non-aqueous dispersion containing rare earth metal powder on the joint end surface of the hot-formed steel plate containing aluminum coating, and then uses a laser wire welding process to weld after the dispersion evaporates, thereby effectively overcoming the above problem. Because during the welding process, the rare earth metal is melted under the heating action of the laser beam and attached to the joint end surface, when the aluminum element in the coating on the surface of the formed steel plate diffuses into the weld under the action of high temperature, these highly active rare earth metal atoms capture aluminum atoms and form solid solutions (such as Al4La, Al2Ce, AlY, AlY3, Al2Y3, etc.), which are distributed in the weld and can play a good role in refining grains and inhibiting crystal dislocation. On the one hand, it prevents aluminum atoms from entering the weld pool and causing the formation of low-strength delta ferrite. On the other hand, the crystal grains in the weld are made finer, while overcoming the problem that the crystal grains in the weld are coarse due to the influence of welding heat, and the problem that dendrites and dendritic structures are easily formed due to the temperature gradient. The finer the crystal grains, the better the mechanical strength and toughness of the weld. The present invention effectively avoids the problem of the aluminum-containing coating deteriorating the mechanical properties of the hot-formed steel weld in the above manner, and the obtained weld joint has both good fracture strength and plasticity.
[0022] (2) The present invention also uses surface-modified rare earth metal powder and volatile non-aqueous dispersion to form a welding joint treatment agent, and propylene glycol or glycerol is added to the volatile non-aqueous dispersion, which helps to reduce the sedimentation of the rare earth metal powder. Furthermore, the present invention also grafts acrylic monomers on the surface of the rare earth metal powder through a pretreatment process, and these monomers gradually polymerize and coat the surface of the rare earth metal powder particles during the subsequent heating process to remove the volatile non-aqueous solvent. On the one hand, after entering the dispersion, the pretreated metal powder has good anti-sedimentation performance due to the affinity between the acrylic polymer on its surface and propylene glycol or glycerol, which facilitates the uniform distribution of the rare earth metal powder on the joint end surface of the steel plate. On the other hand, it helps to prevent the oxidation of rare earth metal powder particles, improve the capture rate of aluminum atoms, and reduce the adverse effects of aluminum atoms on the weld. In addition, during the welding process, the propylene glycol or glycerol can also provide active carbon atoms after being carbonized at high temperature, which helps to reduce the decarburization of the steel plate at the interface of the weld and improve the mechanical strength of the weld joint. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0024] Figure 1 The following is a diagram of a welding specimen used for tensile strength testing in Example 1.
[0025] Figure 2 Graph showing the tensile strength test results of Example 1 below.
[0026] Figure 3 Graph showing the tensile strength test results of Example 2 below.
[0027] Figure 4 Graph showing the tensile strength test results of Example 3 below.
[0028] Figure 5 Graph showing the tensile strength test results of Example 5 below.
[0029] Figure 6 The following is a picture of the welding specimen used for tensile strength test in Example 6. DETAILED DESCRIPTION
[0030] The present invention is further described below in conjunction with specific embodiments. It should be understood that these embodiments and materials are for demonstration purposes only and are not all embodiments. All other embodiments obtained by ordinary technicians in this field based on these embodiments without creative work are within the scope of protection of the present invention. The technical solution of the present invention is further described according to the accompanying drawings and specific embodiments of the specification.
[0031] The welding wire composition used in the laser wire welding process in the following embodiments is shown in Table 1:
[0032] Table 1
[0033]
[0034] Table 2
[0035] .
[0036] Example 1
[0037] A laser wire welding process for hot-formed steel containing an aluminum coating comprises the following steps:
[0038] (1) A hot-formed steel with an Al-Si coating on its surface is used as a welding object, the thickness of which is 2 mm, and the microstructure is mainly lath martensite. The thickness of the Al-Si coating is distributed between 30 and 40 μm.
[0039] (2) Anhydrous ethanol and propylene glycol were mixed in a volume ratio of 1:0.3 and stirred evenly. Rare earth metal powder cerium with a fineness of 120 mesh was then added and ultrasonically dispersed for 15 minutes to obtain a dispersion with a rare earth metal powder content of 40 g / L, which was set aside.
[0040] (3) Apply the dispersion of this embodiment to the end face of the joint to be welded of the hot-formed steel, and apply it once. Then butt the joints of the two hot-formed steel plates, and the gap width between them is 1 mm. After drying naturally for 20 minutes, laser wire welding process is used for welding, the welding power is 6000 W, the welding speed is 0.8 m / min, the shielding gas (argon) flow rate is 10 L / min, and the diameter of the welding wire used for welding is the same as the gap width.
[0041] The hot-formed steel after welding in this embodiment was processed into a tensile specimen by a wire cutting machine, and then a tensile test was carried out using a WDW-100 universal tensile testing machine, with the strain rate set to 0.1s -1 The results are shown in Table 3 below, and the fracture position is located on the parent material (such as Figure 1 As shown in the figure), the tensile strength test results are shown in the figure Figure 2 As shown:
[0042] Table 3
[0043] .
[0044] Example 2
[0045] A laser wire welding process for hot-formed steel containing an aluminum coating comprises the following steps:
[0046] (1) A hot-formed steel with an Al-Si coating on its surface is used as a welding object, the thickness of which is 2 mm, and the microstructure is mainly lath martensite. The thickness of the Al-Si coating is distributed between 30 and 40 μm.
[0047] (2) Mix 100-mesh rare earth metal powder lanthanum and anhydrous ethanol in a ratio of 1g:10ml and stir evenly, then add silane coupling agent (γ-aminopropyltriethoxysilane) and acrylic acid monomer, and the mass fraction of silane coupling agent in the system is 0.035%, and the mass fraction of acrylic acid monomer is 0.18%. Then stir for 30 minutes, filter out the solids and add them to anhydrous ethanol again, the ratio of the two is 1g:10ml. Then heat to 60℃ under stirring and keep warm until constant weight, and the pretreated metal powder is obtained for use.
[0048] (3) Anhydrous ethanol and propylene glycol were mixed in a volume ratio of 1:0.25 and stirred evenly, and then the pretreated metal powder was added and ultrasonically dispersed for 15 minutes to obtain a dispersion with a rare earth metal powder content of 30 g / L, which was set aside.
[0049] (4) Apply the dispersion of this embodiment to the end face of the joint to be welded of the hot-formed steel, and apply it once. Then butt the joints of the two hot-formed steel plates, and the gap width between them is 1 mm. After drying naturally for 20 minutes, laser wire welding process is used for welding, the welding power is 8000 W, the welding speed is 1.5 m / min, the shielding gas (argon) flow rate is 12 L / min, and the diameter of the welding wire used for welding is the same as the gap width.
[0050] The hot-formed steel after welding in this embodiment is processed into a tensile specimen by the same method as in the above-mentioned embodiment 1, and then a tensile test is performed. The results are shown in Table 4 below, and the fracture position is located on the parent material. The tensile strength test results are shown in Table 4 below. Figure 3 As shown:
[0051] Table 4
[0052] .
[0053] Example 3
[0054] A laser wire welding process for hot-formed steel containing an aluminum coating comprises the following steps:
[0055] (1) A hot-formed steel with an Al-Si coating on its surface is used as a welding object, the thickness of which is 2 mm, and the microstructure is mainly lath martensite. The thickness of the Al-Si coating is distributed between 30 and 40 μm.
[0056] (2) Mix yttrium rare earth metal powder with a fineness of 200 mesh and anhydrous methanol in a ratio of 1g:25ml and stir evenly, then add silane coupling agent (octadecyltrimethoxysilane) and acrylic acid monomer, and the mass fraction of silane coupling agent in the system is 0.03%, and the mass fraction of acrylic acid monomer is 0.15%. Then stir for 10 minutes, filter out the solids and add them to anhydrous methanol again, the ratio of the two is 1g:25ml. Then heat to 70℃ under stirring and keep warm until constant weight, and the pretreated metal powder is obtained, which is set aside.
[0057] (3) Anhydrous methanol and propylene glycol were mixed in a volume ratio of 1:0.4 and stirred evenly, and then the pretreated metal powder was added and ultrasonically dispersed for 15 minutes to obtain a dispersion with a rare earth metal powder content of 30 g / L, which was set aside.
[0058] (4) Apply the dispersion of this embodiment to the end face of the joint to be welded of the hot-formed steel, and apply it once. Then butt the joints of the two hot-formed steel plates, and the gap width between them is 0.5 mm. After drying naturally for 20 minutes, laser wire welding process is used for welding, the welding power is 5000 W, the welding speed is 1.0 m / min, the shielding gas (argon) flow rate is 15 L / min, and the diameter of the welding wire used for welding is the same as the gap width.
[0059] The hot-formed steel after welding in this embodiment is processed into a tensile specimen by the same method as in the above-mentioned embodiment 1, and then a tensile test is performed. The results are shown in Table 5 below, and the fracture position is located on the parent material. The tensile strength test results are shown in Table 5 below. Figure 4 As shown:
[0060] Table 5
[0061] .
[0062] Example 4
[0063] A laser wire welding process for hot-formed steel containing an aluminum coating comprises the following steps:
[0064] (1) A hot-formed steel with an Al-Si coating on its surface is used as a welding object, the thickness of which is 2 mm, and the microstructure is mainly lath martensite. The thickness of the Al-Si coating is distributed between 30 and 40 μm.
[0065] (2) Mix ytterbium rare earth metal powder with a fineness of 140 mesh and isopropanol in a ratio of 1g:30ml and stir evenly, then add silane coupling agent (γ-methacryloxypropyltrimethoxysilane) and acrylic acid monomer, and the mass fraction of silane coupling agent in the system is 0.02%, and the mass fraction of acrylic acid monomer is 0.1%. Then stir for 20 minutes, filter out the solids and add them to isopropanol again, the ratio of the two is 1g:30ml. Then heat to 80℃ under stirring and keep warm until constant weight, and the pretreated metal powder is obtained, which is set aside.
[0066] (3) Propanol and propylene glycol are mixed in a volume ratio of 1:0.35 and stirred evenly, and then the pretreated metal powder is added and ultrasonically dispersed for 15 minutes to obtain a dispersion liquid with a rare earth metal powder content of 50 g / L, which is set aside.
[0067] (4) Apply the dispersion of this embodiment to the end face of the joint to be welded of the hot-formed steel, and apply it once. Then butt the joints of the two hot-formed steel plates, and the gap width between them is 1 mm. After drying naturally for 20 minutes, laser wire welding process is used for welding, the welding power is 3000 W, the welding speed is 0.5 m / min, the shielding gas (argon) flow rate is 10 L / min, and the diameter of the welding wire used for welding is the same as the gap width.
[0068] The hot-formed steel after welding in this embodiment was processed into a tensile specimen by the same method as in the above-mentioned embodiment 1, and then a tensile test was performed. The results are shown in Table 6 below, and the fracture position is located on the parent material:
[0069] Table 6
[0070] .
[0071] Example 5
[0072] A laser wire welding process for hot-formed steel containing an aluminum coating comprises the following steps:
[0073] (1) A hot-formed steel with an Al-Si coating on its surface is used as a welding object, the thickness of which is 2 mm, and the microstructure is mainly lath martensite. The thickness of the Al-Si coating is distributed between 30 and 40 μm.
[0074] (2) Mix yttrium rare earth metal powder with a fineness of 200 mesh and anhydrous methanol in a ratio of 1g:25ml and stir evenly, then add silane coupling agent (octadecyltrimethoxysilane), and the mass fraction of silane coupling agent in the system is 0.03%. Then stir for 10 minutes, filter out the solids and add them again to anhydrous methanol in a ratio of 1g:25ml. Then heat to 70℃ under stirring and keep warm until constant weight, and obtain pretreated metal powder for use.
[0075] (3) Anhydrous methanol and propylene glycol were mixed in a volume ratio of 1:0.4 and stirred evenly, and then the pretreated metal powder was added and ultrasonically dispersed for 15 minutes to obtain a dispersion with a rare earth metal powder content of 30 g / L, which was set aside.
[0076] (4) Apply the dispersion of this embodiment to the end face of the joint to be welded of the hot-formed steel, and apply it once. Then butt the joints of the two hot-formed steel plates, and the gap width between them is 0.5 mm. After drying naturally for 20 minutes, laser wire welding process is used for welding, the welding power is 5000 W, the welding speed is 1.0 m / min, the shielding gas (argon) flow rate is 15 L / min, and the diameter of the welding wire used for welding is the same as the gap width.
[0077] The hot-formed steel after welding in this embodiment is processed into a tensile specimen by the same method as in the above-mentioned embodiment 1, and then a tensile test is performed. The results are shown in Table 7 below, and the fracture position is located on the parent material. The tensile strength test results are shown in Table 7 below. Figure 5 As shown:
[0078] Table 7
[0079] .
[0080] Example 6
[0081] A laser wire welding process for hot-formed steel containing an aluminum coating comprises the following steps:
[0082] (1) A hot-formed steel with an Al-Si coating on its surface is used as a welding object, the thickness of which is 2 mm, and the microstructure is mainly lath martensite. The thickness of the Al-Si coating is distributed between 30 and 40 μm.
[0083] (2) The joints of the two hot-formed steel plates are butt-jointed, and the gap width between the two is 1 mm. After natural drying for 20 minutes, laser wire welding is used for welding, with a welding power of 6000 W, a welding speed of 0.8 m / min, a shielding gas (argon) flow rate of 10 L / min, and a welding wire diameter that is the same as the gap width.
[0084] The hot-formed steel after welding in this embodiment is processed into a tensile specimen by the same method as in the above-mentioned embodiment 1, and then a tensile test is performed. The results are shown in Table 8 below, and the fracture position is located in the weld heat affected zone on the parent material (such as Figure 6 shown):
[0085] Table 8
[0086] .
[0087] Example 7
[0088] A laser wire welding process for hot-formed steel containing an aluminum coating comprises the following steps:
[0089] (1) A hot-formed steel with an Al-Si coating on its surface is used as a welding object, the thickness of which is 2 mm, and the microstructure is mainly lath martensite. The thickness of the Al-Si coating is distributed between 30 and 40 μm.
[0090] (2) Add rare earth metal powder cerium with a fineness of 120 mesh into anhydrous ethanol and perform ultrasonic dispersion treatment for 15 minutes to obtain a dispersion with a rare earth metal powder content of 40 g / L for later use.
[0091] (3) Apply the dispersion of this embodiment to the end face of the joint to be welded of the hot-formed steel, and apply it once. Then butt the joints of the two hot-formed steel plates, and the gap width between them is 1 mm. After drying naturally for 20 minutes, laser wire welding process is used for welding, the welding power is 6000 W, the welding speed is 0.8 m / min, the shielding gas (argon) flow rate is 10 L / min, and the diameter of the welding wire used for welding is the same as the gap width.
[0092] The hot-formed steel after welding in this embodiment was processed into a tensile specimen by the same method as in the above-mentioned embodiment 1, and then a tensile test was performed. The results are shown in Table 9 below, and the fracture position is located in the weld area:
[0093] Table 9
[0094] .
[0095] Example 8
[0096] A laser wire welding process for hot-formed steel containing an aluminum coating comprises the following steps:
[0097] (1) A hot-formed steel with an Al-Si coating on its surface is used as a welding object, the thickness of which is 2 mm, and the microstructure is mainly lath martensite. The thickness of the Al-Si coating is distributed between 30 and 40 μm.
[0098] (2) Mix 100-mesh rare earth metal powder lanthanum and anhydrous ethanol in a ratio of 1g:10ml and stir evenly, then add acrylic acid monomer, and the mass fraction of acrylic acid monomer in the system is 0.18%. Then stir for 30 minutes, filter out the solids and add them again to anhydrous ethanol in a ratio of 1g:10ml. Then heat to 60℃ and keep warm to constant weight under stirring to obtain pretreated metal powder, which is set aside.
[0099] (3) Anhydrous ethanol and propylene glycol were mixed in a volume ratio of 1:0.25 and stirred evenly, and then the pretreated metal powder was added and ultrasonically dispersed for 15 minutes to obtain a dispersion with a rare earth metal powder content of 30 g / L, which was set aside.
[0100] (4) Apply the dispersion of this embodiment to the end face of the joint to be welded of the hot-formed steel, and apply it once. Then butt the joints of the two hot-formed steel plates, and the gap width between them is 1 mm. After drying naturally for 20 minutes, laser wire welding process is used for welding, the welding power is 8000 W, the welding speed is 1.5 m / min, the shielding gas (argon) flow rate is 12 L / min, and the diameter of the welding wire used for welding is the same as the gap width.
[0101] The hot-formed steel after welding in this embodiment was processed into a tensile specimen by the same method as in the above-mentioned embodiment 1, and then a tensile test was performed. The results are shown in Table 10 below, and the fracture position is located on the parent material:
[0102] Table 10
[0103] .
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A laser wire welding process for hot-formed steel containing aluminum coating, characterized in that: The steps include: (1) Apply a volatile non-aqueous dispersion containing rare earth metal powder on the joint end surface of the aluminum-coated hot-formed steel plate to be welded; (2) then butting the joints of the two hot-formed steel plates together to form a gap between them; and after the dispersion liquid has evaporated, laser wire welding is used to perform welding; In step (1), the content of the rare earth metal powder in the dispersion is 30-50 g / L, and the fineness of the rare earth metal powder is not less than 100 mesh; In step (1), the rare earth metal includes at least one of lanthanum, cerium, yttrium, samarium, and ytterbium; In step (1), the volatile non-aqueous dispersion comprises a mixture of at least one of anhydrous methanol and anhydrous ethanol and propylene glycol or glycerol, and the volume ratio of the two is 1:0.25-0.4; In step (1), the rare earth metal powder is a pre-treated metal powder prepared by the following method: (i) dispersing the rare earth metal powder into a volatile non-aqueous solvent, then adding a silane coupling agent and an acrylic acid monomer and stirring, and separating the solid matter after completion; (ii) adding the solid matter into a volatile non-aqueous solvent again, and heating and stirring until the non-aqueous solvent is volatilized and removed, thereby obtaining the pre-treated metal powder; In steps (i) and (ii), the material-liquid ratio of the rare earth metal powder, the solid and the non-aqueous solvent is 1 g: 10-30 ml; the non-aqueous solvent comprises at least one of anhydrous methanol, anhydrous ethanol and isopropanol; In step (i), the mass fraction of the silane coupling agent in the non-aqueous solvent is 0.02-0.035%; the mass fraction of the acrylic acid monomer in the non-aqueous solvent is 0.1-0.18%.
2. The laser wire welding process for hot-formed steel containing aluminum coating according to claim 1 is characterized in that: In step (2), the width of the gap is 0.5-1 mm.
3. The laser wire welding process for hot-formed steel containing aluminum coating according to claim 1, characterized in that: In step (2), the power of the laser wire-filling welding process is 3000-8000 W; the welding speed is 0.5-1.5 m / min, and the shielding gas flow rate is 10-15 L / min.
4. The laser wire welding process for hot-formed steel containing aluminum coating according to claim 1, characterized in that: In step (i), the stirring time is not less than 10 min.
5. The laser wire welding process for hot-formed steel containing aluminum coating according to any one of claims 1 to 4, characterized in that: In step (ii), the heating temperature is 60-80°C.
Citation Information
Patent Citations
Alloy powder used for improving flexibility of dual-phase steel laser welding joints and application method of alloy powder
CN103521762A
Welding active agent for aluminum alloy part in grain throwing machine
CN112157372A